1994
DOI: 10.1037/0033-2909.116.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Parental caregiving and child externalizing behavior in nonclinical samples: A meta-analysis.

Abstract: A meta-analysis of 47 studies was used to shed light on inconsistencies in the concurrent association between parental caregiving and child externalizing behavior. Parent-child associations were strongest when the measure of caregiving relied on observations or interviews, as opposed to questionnaires, and when the measure tapped combinations of parent behaviors (patterns), as opposed to single behaviors. Stronger parent-child associations were also found for older than for younger children, and for mothers th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

47
664
10
23

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 771 publications
(744 citation statements)
references
References 147 publications
47
664
10
23
Order By: Relevance
“…Parenting that constrains, invalidates, and manipulates children's psychological and emotional experience and expression is also related to both internalizing and externalizing symptoms 1 (Barber, 1996). A meta-analysis of 47 studies found that higher levels of coercive control in the family were related to problems of undercontrol on the part of children, particularly more aggressive and noncompliant behavior (Rothbaum & Weisz, 1994), a relation that is argued to be bidirectional.…”
Section: Mental Healthmentioning
confidence: 99%
“…Parenting that constrains, invalidates, and manipulates children's psychological and emotional experience and expression is also related to both internalizing and externalizing symptoms 1 (Barber, 1996). A meta-analysis of 47 studies found that higher levels of coercive control in the family were related to problems of undercontrol on the part of children, particularly more aggressive and noncompliant behavior (Rothbaum & Weisz, 1994), a relation that is argued to be bidirectional.…”
Section: Mental Healthmentioning
confidence: 99%
“…Parents who are high in warmth and positive emotion, and low in the expression of disapproval, hostility, and other negative emotions directed toward their children, tend to have socially competent, adjusted children who are also skilled in social understanding (Lindahl, 1998;Matthews, Woodall, Kenyon, & Jacob, 1996;Rothbaum & Weisz, 1994;Rubin, Hastings, Chen, Stewart, & McNichol, 1998;Scaramella, Conger, & Simons, 1999). In addition, both parental and family expressiveness, especially positive expressivity, have been associated with children's social competence, emotional understanding, positive emotionality, prosocial behavior, and self-esteem (Boyum & Parke, 1995;Bronstein et al, 1993;Cassidy, Parke, Butkovsky, & Braungart, 1992;Halberstadt et al, 1999).…”
Section: Emotional Climate Of the Family: Parenting And Family Emotiomentioning
confidence: 99%
“…Parenting characteristics have been the most frequently considered environmental antecedents of child behavior problems. Like temperament variables, parenting variables have been found to show direct, main-effects links with child adjustment (Hetherington & Martin, 1986; G. R. Patterson, Reid, & Dishion, 1992;Rothbaum & Weisz, 1994), And also like temperament, the links are of a typically modest-to-moderate order, with correlations in the range of .2 to .4 (e.g., see Rothbaum & Weisz, 1994). Not only current systems theories but also empirical findings of limited maineffects relations call for the study of Temperament × Environment interactions.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%